(untitled) (Acta Entomologica Serbica, 2014)
Predatory hoverflies are useful pollinators in their adult stage and present a natural enemy of plant pests, especially of aphids in their larval stage.The observations were made with the application of the following methods of catching: check of all leaves of 20 tobacco stalks; and check of 100 tobacco leaves in 10-day intervals during the entire period of vegetation of the tobacco. The collected material was further nourished and analysed under laboratory conditions. The tobacco crop was attacked only by Myzus persicae Sulzer and larvae were reared on tobacco leaves infested with M. persicae in Petri dishes.During a period of three years Sphaerophoria scripta Linnaeus, Sphaerophoria rueppelli Wiedemann and Scaeva pyrastri Linnaeus are represented in great numbers. Under laboratory conditions the larvae from the species S. scripta consumed from 300 up to 365 aphids from the species M. persicae; the larvae from the species S. rueppelli, 280-321 aphids; and those of the species S. pyrastri, 280-563 aphids. These data show their great capacity for eating aphids. With their great voracity, and to preserve their own kind, they control the population of aphids on tobacco, and so have a great impact on the tobacco biocenoses. The aphidophagous Syrphidae are the main predators and they are ranged on the third trophic level of the food chain: tobacco leaf - aphids - aphidophagous hoverflies. In the complex food chain the aphidophagous Syrphidae are being parasitized by many species of parasites and because of that their ecological and economic use is lesser.During the laboratory analyses from 2003-2005 we detected ten parasitic species of the order Hymenoptera, ecloded in the pupae of the aphidophagous Syrphidae: Pachyneuron grande Thomson, Pachyneuron cf. grande Thomson, Syrphophagus aeruginosus Dalman, Diplazon laetatorius Fabricius, Diplazon sp. 2, Diplazon sp. 3, Homotropus sp. 1, Homotropus sp. 2, Sussaba sp. 1, Promethes sp. 1.The parasitism has a negative impact on reducing the population of the future generation of the species Syrphidae. The species S. scripta, S. rueppelli and S. pyrastri can be used as integral protectors of the tobacco leaf aphids, because of their great numbers and their great voracity.